ANALISIS EXPORT BASE TERHADAP PERTUMBUHAN EKONOMI DI PROPINSI DATII JAWA TIMUR PERIODE 1997-2001 - Sri Rahayu; Daryono Soebagiyo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2004)
The growth of many economic sectors can support mutually. Therefore, it needs to analyze the sectors which have potency to be basis sector and non-basis sectors. Some activities of economic sector in an area is basic, it is means that its growth rises and determines development of the area entirely, while activities of non-basic economic sector is consequence of the development entirely. More further, to make clearer the identification to the activity of economic sector, it needs to analyze the large of multiplier of the basis sector activity to the region income and the leaking level of region income which occurred as result of basis sector activity.The research area is East Java province, and object of PRDB research sector ally in East Java province in 1997-2001 and PDB Indonesia is as references. This research is explorative. To analyze the basis sector is used LQ method.